2021
DOI: 10.3390/molecules26082354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seven Essential Oils as Seed Treatments against Seedborne Fungal Pathogens of Cucurbita maxima

Abstract: Essential oils are gaining interest as environmentally friendly alternatives to synthetic fungicides for management of seedborne pathogens. Here, seven essential oils were initially tested in vivo for disinfection of squash seeds (Cucurbita maxima) naturally contaminated by Stagonosporopsis cucurbitacearum, Alternaria alternata, Fusarium fujikuro, Fusarium solani, Paramyrothecium roridum, Albifimbria verrucaria, Curvularia spicifera, and Rhizopus stolonifer. The seeds were treated with essential oils from Cymb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
2
12
0
2
Order By: Relevance
“…In this perspective, several works are found that, although not directly targeting targets external to seeds, validate, in a broad sense, the strategy of using essential oils in the management of plant diseases (Lozada et al;Moumni et al, 2021;Grzanka et al, 2021) and support the present study.…”
Section: Rolfsiisupporting
confidence: 84%
“…In this perspective, several works are found that, although not directly targeting targets external to seeds, validate, in a broad sense, the strategy of using essential oils in the management of plant diseases (Lozada et al;Moumni et al, 2021;Grzanka et al, 2021) and support the present study.…”
Section: Rolfsiisupporting
confidence: 84%
“…Chen et al (2014) demonstrated the effectiveness of a citronella (Cymbopogon nardus) essential oil on A. alternate in in vitro and in vivo assays. Moumni et al (2021) tested in vivo seven essential oils for disinfection of squash seeds (Cucurbita maxima) that had been naturally contaminated with Stagonosporopsis cucurbitacearum, Alternaria alternata, Fusarium fujikuro, Fusarium solani, Paramyrothecium roridum, Albifimbria verrucaria, Curvularia spicifera, and Rhizopus stolonifer. The seeds were treated with essential oils produced from Cymbopogon citratus, Lavandula dentata, Lavandula hybrida, Melaleuca alternifolia, Laurus nobilis, and Origanum majorana (#1 and #2).…”
Section: Use Of Natural Compounds -Plant Extracts and Oilsmentioning
confidence: 99%
“…The potential use in agriculture is further encouraged by their low or no toxicity against vertebrates, easy extractability and eco-compatibility, biodegradability ( Zygadlo and Grosso, 1995 ) and the lack of persistence in soil and water ( Misra and Pavlostathis, 1997 ; Isman, 2000 ; Isman and Machial, 2006 ). Indeed, recent studies ( Riccioni and Orzali, 2011 ; Sharma et al., 2017 ) have shown that essential oils can reduce growth of some pathogenic fungi, and their potential applications in seed treatment are still being studied and developed ( Moumni et al., 2021 ; Kesraoui et al., 2022 ). To our knowledge, no data are reported in literature on wheat seed treatment with clove essential oil against common bunt under field conditions.…”
Section: Introductionmentioning
confidence: 99%